CLASSIFICATION OF FUNDAMENTAL RIGHTS AND FREEDOMS – A DIACHRONIC APPROACH AND CURRENT TRENDS - NICOLAE PAVEL (Challenges of the Knowledge Society)
What seems relevant to this study is the current trend of the classification of rights and fundamental freedoms according to the universal and indivisible values criterion, criterion established by the Charter of Fundamental Rights of European Union. Taking as reference the new scientific criterion, we propose a diachronic approach classification in terms of rights and fundamental freedoms in the light of juridical doctrine and in terms of European and international documents on human rights and citizen. It is necessary to point out from the beginning that the classification of fundamental rights and freedoms does not imply a hierarchy and, from this point of view we consider it necessary to classify or group the rights and fundamental freedoms by scientific criteria, at least from the following reasons: it facilitates their explanation, their general characteristics and basic understanding, and the progress of their content and scope. By this approach, the proposed study opens a complex and complete vision, but not exhaustive on the classification classification of the current human and citizen rights. That is why the study begins with preliminary specifications that establish the terminology used in the content of the study, the correlation between domestic regulations and international human rights and the relationship between law and the law of European Union. Following a key – scheme we analyse successively the two major parts of the study, namely the classification of fundamental rights and freedoms in terms of constitutional doctrine and the doctrine of human rights, and the current trends on the classification of fundamental rights and freedoms.